KONSEP AL-QUR’AN TENTANG METODE PENDIDIKAN ISLAM - Mardeli Mardeli (Ta'dib: Jurnal Pendidikan Islam, 2011)
AbstractAl-Quran as a source of inspiration and education have the breadth of the concept of engineering education. The issue of education in the Qur'an is not organized in one letter, but there are many letters and to formulate the sense and purpose of education is required ijtihad. One of the concepts of the Qur'an is the concept of educational methods. There are several methods of education are presented in the Qur'an, namely: a lecture, methods now play in the story, question and answer method, research methods, and methods of demonstration. Keywords: Al-Qur'an, methods, education